Alecsandri’s Work and the Romanian Language Literary in the Nineteenth Century - Mihaela Nicoleta, Ichim-Radu (Eximia, 2021)
The poet Vasile Alecsandri has always had the conscience of the writer-citizen, his entire work being directly addressed to the public. His desire “to write” was the starting point in opening new paths, in literature in general, and in historical literature in particular. The importance of language in the destiny of the Romanian people was defined by Alecsandri as the most precious treasure that children inherit from their parents, the most sacred deposit left by past generations.